Self‐Supporting 3D Carbon Nitride with Tunable n → π* Electronic Transition for Enhanced Solar Hydrogen Production. Issue 49 (10th October 2021) - An, Sufeng; Zhang, Guanghui; Li, Keyan; Huang, Zhennan; Wang, Xiang; Guo, Yongkang; Hou, Jungang; Song, Chunshan; Guo, Xinwen
Abstract: Self‐supporting 3D (SSD) carbon nitrides (UCN‐ X, X  = 600–690; where X represents the pyrolytic temperature) consisting of curved layers, with plenty of wrinkles and enlarged size, are synthesized via a facile stepwise pyrolytic strategy. Such unique features of the SSD structure exhibiting dramatically improved charge mobility, extended π‐conjugated aromatic system, and partial distortion of heptazine‐based skeleton can not only keep the easier activation of the intrinsic π →  π* electronic transition but also awaken the n → π* electronic transition in carbon nitride. The n → π* electronic transition of UCN‐ X can be controllably tuned through changing the pyrolytic temperature, which can greatly extend the photoresponse range to 600 nm. More importantly, the change regularity of H2 evolution rates is highly positive, correlated with the change tendency of n → π* electronic transition in UCN‐ X, suggesting the positive contribution of n → π* electronic transition to enhancing photocatalytic activity. The UCN‐670, with optimal structural and optical properties, presents enhanced H2 evolution rate up to 9230 µmol g −1 h −1 (Pt 1.1 wt%). This work realizes the synergistic optimization of optical absorption and exciton dissociation via fabricating an SSD structure. It offers a new strategy for the development of novel carbon nitride materials for efficient photocatalytic reactions. Abstract : Self‐supporting 3D (SSD) polymeric carbon nitride (PCN), with tunable n → π* electronic transition, is successfully synthesized via a facile stepwise pyrolytic strategy. The synergistic optimization of the SSD structure and n → π* electronic transition in PCN significantly advance the exciton dissociation and optical absorption, leading to enhanced visible‐light H2 evolution activity in the spectral region above 500 nm.